Perancangan Digitalisasi Tracer Study Berbasis Web Menggunakan Metode Rapid Application Devolopmant - Zaenal Mustofa; Arsito Ari Kuncoro; Febryantahanuji, Febryantahanuji; Yussi Anggraini (Lembaga Pengembangan Kinerja Dosen, 2023)
This Information System makes a valuable contribution to educational institutions that wish to betterunderstand their educational and career paths, so that alumni can make more informed decisions for continuous improvement. This is an important step in encouraging data-based decision making and improving the quality of education. Baiturrahman Center Semarang does not yet have atracer study system so the school has difficulty getting alumni data as well. Based on these problems,the Islamic Center Baiturrahman Semarang Vocational School requires a Tracer Study Digitalization Information System designed using the Rapid Application Development (RAD)method. RAD is applied in order to understand, analyze and integrate project or system developmentsquickly and efficiently. from this research, namely a digitalization information system based on tracerstudy, which is expected to help the Baiturrahman Islamic Center Vocational School Semarang inimproving its development.